The electrochemical oxidation of hydrogen peroxide on nickel electrodes in phosphate buffer solutions : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Chemistry at Massey University, Palmerston North, New Zealand - Nairn, Justin John (Massey University, 2000)
The electrochemical oxidation of hydrogen peroxide was studied at nickel electrodes in phosphate buffer solutions. This reaction is of interest because of its possible use in the construction of devices for the electrochemical detection of hydrogen peroxide. The devices developed could be advantageous in many industrial and medical processes. Using the electrochemical technique, staircase potentiometry, the activity of the nickel electrode in catalysing hydrogen peroxide oxidation was evaluated over a range of bulk hydrogen peroxide concentrations, rotation rates, electrode potentials, temperatures, buffer concentrations and pH. A mechanism was developed to account for the observed activity. This was based on a previous model developed for the electrochemical oxidation of hydrogen peroxide at platinum electrodes [1-6], The mechanism involved H2O2 interaction with binding sites on the surface of the electrode. These were initially identified as a nickel phase oxide, Ni(OH)2. Later, the involvement of buffer phosphate species HPO4- was identified. Hydrogen peroxide is adsorbed onto the binding site to form the complex NiBs H2O2. This complex then undergoes an internal charge transfer to form a reduced nickel site, liberating the products water and oxygen. The binding site regenerates electrochemically to give rise to an amperometric signal with the release of protons. A side reaction was proposed which involved an interaction between the binding sites and dioxygen. This interaction competitively inhibited the binding of H2O2. A rate equation was derived to account for all the surface sites involved in the proposed reaction mechanism. The kinetic, equilibrium and thermodynamic constants of the resulting model were optimised by a SIMPLEX procedure. These constants were in turn used in conjunction with the rate equation to produce synthetic responses, which were then compared to the observed steady-state response. A satisfactory fit was found over the entire range of conditions studied. This supported the proposition that the mechanism was appropriate. The equilibrium constants were found to be potential invariant, with K1= 4.43 × 10-3 and K4 = 0.360 m3 mol-1 at 20°C. The former, K1, was exothermic, with ΔH = -28.32 kJ K-1 between 5 and 25°C, and became significantly more exothermic, with ΔH = -198.33 kJ K-1 between 25 and 35°C. In contrast, K4 was slightly endothermic, with ΔH = -16.5 kJ K-1 over the temperature range. One rate constant could be approximated to be potential invariant, k3N = 7.99 × 10-4 mol m-2s-1 at 20°C. Whereas, the other, k2N, varied with potential. Both rate constants were endothermic with pseudo-activation energies for k3N being 24.3 kJ mol-1 and for k2N ranging between 130-80 kJ mol-1 (depending on electrode potential). An optimum pH region for the study of H2O2 oxidation at nickel was found to be between pH 4 and 9. Above and below these bounds competitive reactions occurred that were not attributable to hydrogen peroxide and insignificant rates of reaction for electrochemical measurement were found. The phosphate species HPO4-2 was identified as being involved in the oxidative mechanism. The nature of this involvement was complex, with HPO4-2 both inhibiting and facilitating H2O2 oxidation, depending on surface concentration. To accommodate this, the proposed mechanism was further modified to include this involvement. It was proposed that HPO4-2 was required to form the H2O2 binding site from a nickel precursor site on the electrode surface. However, the complexation of a second HPO4-2 to this site would inhibit H2O2 binding. The work presented in this thesis represents a fundamental study into the electrochemical behaviour of hydrogen peroxide at nickel electrodes. This behaviour has been clearly identified over a range of temperatures, hydrodynamic conditions, buffer compositions and concentrations. This enabled a new and comprehensive mechanism, for the oxidation of hydrogen peroxide at nickel electrode, to be developed
Keywords: Hydrogen peroxide -- Oxidation; Electrolytic oxidation